The Influence of Corporate Governance on Financial Performance: Evidence from Global Markets - Katharaj , I.; Jagga, Megha; Kalra, Hitesh; Srivastava , Dr. Garima; Agarwal , Dr. Varsha; Das, Dr. JyotiRanjan; Bhavya , Dr.B. (International Journal of Accounting and Economics Studies, 2025)
Corporate governance significantly influences economic growth and financial market stability. There has been ongoing debate among scholars regarding the connections between corporate governance, market value, and company performance, leading to different findings. This study was a correlational study intended to investigate corporate governance practices and financial success with reference to agency theory and institutional theory. It tested several different dimensions of corporate governance, including CEO pay, ownership structure, board size, board independence, and the existence of board committees. As history shows, corporate governance models and philosophies are constantly evolving. One reason for this shift is the growing emphasis on profit over social responsibility, which often takes a backseat. Companies worldwide are now striving to weave governance into their corporate frameworks. With the rise of capitalism, corporations have gained significant power, leading governments to relinquish some control to their influence. Today, businesses stand as formidable institutions, manifesting in various forms, sizes, and capacities across the globe. Their governance practices have a profound impact on economies and the broader social landscape. Unfortunately, many companies have seen their market value decline, causing shareholders to lose confidence. Effective corporate governance is defined by legitimacy, accountability, and competence, all while upholding the law and respecting human rights in policy and delivery service. The Cadbury report simplifies the concept by illustrating how corporate governance oversees and regulates business operations.